2023
DOI: 10.3389/fphar.2022.1076392
|View full text |Cite
|
Sign up to set email alerts
|

Successful establishment and five-year sustainability of a neonatal-specific antimicrobial stewardship program in a low middle-income country

Abstract: Introduction: Antibiotic use varies substantially among neonatal intensive care units (NICUs) without any appreciable impact on outcomes. An increased use of antimicrobials has been reported in low-middle income countries. This raises the concern for potential overuse of antibiotics in a fragile patient population, thus increasing the rates of multidrug resistant organisms and affecting the developing microbiome. The presence of a neonatal-specific antimicrobial stewardship program can aid with the judicious u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Finally, in a recent prospective, single-center quality improvement project conducted at the American University of Beirut Medical Center (Lebanon), it has been demonstrated that a neonatal-specific antimicrobial stewardship program is associated with a significant and sustained decrease in antimicrobial use (−63% ampicillin use and −79% gentamicin use) [ 93 ].…”
Section: Antimicrobial Stewardship Programs In Nicus Around the Worldmentioning
confidence: 99%
“…Finally, in a recent prospective, single-center quality improvement project conducted at the American University of Beirut Medical Center (Lebanon), it has been demonstrated that a neonatal-specific antimicrobial stewardship program is associated with a significant and sustained decrease in antimicrobial use (−63% ampicillin use and −79% gentamicin use) [ 93 ].…”
Section: Antimicrobial Stewardship Programs In Nicus Around the Worldmentioning
confidence: 99%